Reconstruction of the Scapholunate Ligament Using Capitohamate Bone-Ligament-Bone - Nakamura, Toshiyasu; Abe, Koji; Iwamoto, Takuji; Ochi, Kensuke; Sato, Kazuki (Journal of Wrist Surgery, 2015)
Background The biomechanical properties of the capitohamate (CH) ligament are equivalent to those of the scapholunate (SL) interosseous ligament. We reconstructed the SL ligament using the CH bone-ligament-bone substitute for chronic injury of the SL ligament.Patients and Methods Beginning in 2008, 15 wrists of 14 patients with an average age of 38 years underwent this procedure with a minimum follow-up of 2 years. Thirteen wrists had an SL joint gap more than 3 mm, and two had a complete SL ligament disruption with a severe dorsal intercalated segment instability (DISI) deformity. Kirschner wires (K-wires) were removed 8 weeks after the surgery, then active ROM exercise began. Pain (on visual analog scale [VAS]), wrist motion (angle), radiographic characteristics, such as SL gap (mm) and SL angle, and Modified Mayo Wrist Score (MMWS) were evaluated.Technique The SL joint was reduced by manipulation or with the use of joysticks, then temporary fixed with K-wires. A dorsal trough was then made between the scaphoid and the lunate. The proximal half of the CH ligament was harvested with attached bone from the capitate and hamate (CH bone-ligament-bone), inset into the SL trough, and fixed firmly with 1.2-mm diameter titanium screws in the scaphoid and lunate, respectively.Results The VAS improved from 77 preoperatively to 12 postoperatively. The average wrist extension/flexion was 74°/60°. There was no ossification of the reconstructed SL at the final follow-up. The SL gap improved from an average of 4.8 mm to an average of 2.1 mm, and the SL angle changed from 67° to 55°. The MMWS improved to 82 points postoperatively from a preoperative average of 47 with eight excellent, five good, and two fair results.
Keywords: scapholunate ligament; capitohamate ligament; reconstruction; chronic injury